Studies on metabolism in macrophages - Newsholme, P; Philip Newsholme (1987)
﻿ A general metabolic profile of macrophages was established by measurement of maximum catalytic activities of enzymes in energy-producing pathways and rates of utilisation of glucose, glutamine, fatty acids and ketone bodies under various conditions. It was found that glucose, glutamine and fatty acids can be used to satisfy the energy requirement of the cell. Although a significant proportion of utilised glutamine or fatty acid was converted to C02 by the macrophage, most glucose was not oxidised and was converted, almost stoichiometrically, to lactate. Utilised fatty acids were not only oxidised by the macrophage, but were incorporated into cellular lipid (mainly triacylglycerol and phospholipid). The triacylglycerol rich macrophage was shown to be able to release fatty acids into the culture medium. The importance of glutamine in macrophages was indicated from the high activity of phosphate-dependent glutaminase. Glutamine is probably metabolised by the following enzymes in macrophages: phosphate-dependent glutaminase, aspartate aminotransferase (or other amino acid aminotransferases), oxoglutarate dehydrogenase followed by enzymes of the TCA cycle and metabolism of oxaloacetate by phosphoenolpyruvate carboxykinase. Pyruvate derived via this pathway may be metabolised via pyruvate dehydrogenase or pyruvate carboxylase. A study of the sub-cellular distribution of some of these enzymes suggested that phosphate-dependent glutaminase has a cytosolic as well as a mitochondrial localisation. Further characterisation suggested that the non-mitochondrial activity could be associated with the plasma membrane. To the author's knowledge, this is the first report of a non-mitochondrial localisation for phosphate-dependent glutaminase. Glutaminase was shown to be activated by phosphate and inhibited by glutamate and 2-oxoglutarate. Significant inhibition of glutaminase occurred only at high concentrations of these compounds. Glucose and glutamine were utilised at very high rates by the macrophage, but were not fully oxidised even though the cells were incubated in aerobic conditions. The significance of these high rates of utilisation to the macrophage is discussed.